Pengaruh Beban Kerja, Kompensasi Dan Kepuasan Kerja Terhadap Produktivitas Kerja (Studi Pada KUD Pakis) - Putri Rahmatania; Agus Widarko; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine the effect of workload, compensation and job satisfaction on work productivity at KUD Pakis simultaneously or partially. This research uses quantitative research with a descriptive approach. The population in this study were employees of KUD Pakis. The sample in this study was 33 employees of KUD Pakis. The sampling technique used was saturated sample or total sampling. Data analysis used multiple linear regression analysis processed with SPSS 20 software. The data collection method used was a questionnaire. The results showed that workload, compensation, and job satisfaction simultaneously influence work productivity, workload does not affect work productivity, compensation has an effect on work productivity, and job satisfaction has an effect on work productivity. Keywords: Workload, Compensation, Job Satisfaction and Work Productivity